Melatonin Sensitizes OVCAR-3 Cells to Cisplatin through Suppression of PI3K/Akt Pathway : Melatonin Sensitizes OVCAR-3 Cells to Cisplatin - Baghal-Sadriforoush, Sahar; Bagheri, Morteza; Abdi Rad, Isa; Sotoodehnejadnematalahi, Fattah (Cellular and Molecular Biology, 2022)
This study examined the effect of melatonin on oxidative stress, expression of pro-apoptotic protein, anti-apoptotic proteins, and the activity of the PI3K/Akt signaling pathway in the human ovarian cancer cell line (OVCAR3). OVCAR3 cells were treated with cisplatin, melatonin, cisplatin + melatonin, and siRNA Akt. Reactive oxygen species levels were assessed. The expression of the proteins was determined by Western blot. Melatonin administration significantly increased intracellular ROS generation, the cleavage of caspase 3 and decreased phosphorylation of Akt. Combination therapy of cisplatin and melatonin increases apoptosis in the OVCAR-3 cells by inhibiting of PI3K/Akt signaling pathway and exacerbating oxidative stress.